Book Review: Tampère, C.M.J., Viti, F. and Immers, L. H. (eds.): New Developments in Transport Planning: Advances in Dynamic Traffic Assignment - Bekhor, Shlomo (European Journal of Transport and Infrastructure Research, 2011)
This book contains a selection of contributions from the second Dynamic Traffic Assignment (DTA) Symposium held at the Katholieke Universiteit Leuven, Belgium, in June 2008. The nineteen individual chapters of the book are suitably classified in four distinct parts, providing a coherent state-of-the-art overview of fundamental DTA research and practice. The international experts that contribute to the book are leading researchers in the field, and provide both wide-spread reviews and fresh looks on the various issues related to DTA.